Design of Nanoparticles in Cancer Therapy Based on Tumor Microenvironment Properties - Bita Mahdavi Firouzabadi; Maria Rosa Gigliobianco; Joice Maria Joseph; Roberta Censi; Piera Di Martino (MDPI AG, 2022)
Cancer is one of the leading causes of death worldwide, and battling cancer has always been a challenging subject in medical sciences. All over the world, scientists from different fields of study try to gain a deeper knowledge about the biology and roots of cancer and, consequently, provide better strategies to fight against it. During the past few decades, nanoparticles (NPs) have attracted much attention for the delivery of therapeutic and diagnostic agents with high efficiency and reduced side effects in cancer treatment. Targeted and stimuli-sensitive nanoparticles have been widely studied for cancer therapy in recent years, and many more studies are ongoing. This review aims to provide a broad view of different nanoparticle systems with characteristics that allow them to target diverse properties of the tumor microenvironment (TME) from nanoparticles that can be activated and release their cargo due to the specific characteristics of the TME (such as low pH, redox, and hypoxia) to nanoparticles that can target different cellular and molecular targets of the present cell and molecules in the TME.